Multiplicity of cerebrospinal fluid functions: New challenges in health and disease - Johanson, Conrad E (BioMed Central, 2008)
This review integrates eight aspects of cerebrospinal fluid (CSF) circulatory dynamics: formation rate, pressure, flow, volume, turnover rate, composition, recycling and reabsorption. Novel ways to modulate CSF formation emanate from recent analyses of choroid plexus transcription factors (E2F5), ion transporters (NaHCO(3 )cotransport), transport enzymes (isoforms of carbonic anhydrase), aquaporin 1 regulation, and plasticity of receptors for fluid-regulating neuropeptides. A greater appreciation of CSF pressure (CSFP) is being generated by fresh insights on peptidergic regulatory servomechanisms, the role of dysfunctional ependyma and circumventricular organs in causing congenital hydrocephalus, and the clinical use of algorithms to delineate CSFP waveforms for diagnostic and prognostic utility. Increasing attention focuses on CSF flow: how it impacts cerebral metabolism and hemodynamics, neural stem cell progression in the subventricular zone, and catabolite/peptide clearance from the CNS. The pathophysiological significance of changes in CSF volume is assessed from the respective viewpoints of hemodynamics (choroid plexus blood flow and pulsatility), hydrodynamics (choroidal hypo- and hypersecretion) and neuroendocrine factors (i.e., coordinated regulation by atrial natriuretic peptide, arginine vasopressin and basic fibroblast growth factor). In aging, normal pressure hydrocephalus and Alzheimer's disease, the expanding CSF space reduces the CSF turnover rate, thus compromising the CSF sink action to clear harmful metabolites (e.g., amyloid) from the CNS. Dwindling CSF dynamics greatly harms the interstitial environment of neurons. Accordingly the altered CSF composition in neurodegenerative diseases and senescence, because of adverse effects on neural processes and cognition, needs more effective clinical management. CSF recycling between subarachnoid space, brain and ventricles promotes interstitial fluid (ISF) convection with both trophic and excretory benefits. Finally, CSF reabsorption via multiple pathways (olfactory and spinal arachnoidal bulk flow) is likely complemented by fluid clearance across capillary walls (aquaporin 4) and arachnoid villi when CSFP and fluid retention are markedly elevated. A model is presented that links CSF and ISF homeostasis to coordinated fluxes of water and solutes at both the blood-CSF and blood-brain transport interfaces. OUTLINE: 1 Overview 2 CSF formation 2.1 Transcription factors 2.2 Ion transporters 2.3 Enzymes that modulate transport 2.4 Aquaporins or water channels 2.5 Receptors for neuropeptides 3 CSF pressure 3.1 Servomechanism regulatory hypothesis 3.2 Ontogeny of CSF pressure generation 3.3 Congenital hydrocephalus and periventricular regions 3.4 Brain response to elevated CSF pressure 3.5 Advances in measuring CSF waveforms 4 CSF flow 4.1 CSF flow and brain metabolism 4.2 Flow effects on fetal germinal matrix 4.3 Decreasing CSF flow in aging CNS 4.4 Refinement of non-invasive flow measurements 5 CSF volume 5.1 Hemodynamic factors 5.2 Hydrodynamic factors 5.3 Neuroendocrine factors 6 CSF turnover rate 6.1 Adverse effect of ventriculomegaly 6.2 Attenuated CSF sink action 7 CSF composition 7.1 Kidney-like action of CP-CSF system 7.2 Altered CSF biochemistry in aging and disease 7.3 Importance of clearance transport 7.4 Therapeutic manipulation of composition 8 CSF recycling in relation to ISF dynamics 8.1 CSF exchange with brain interstitium 8.2 Components of ISF movement in brain 8.3 Compromised ISF/CSF dynamics and amyloid retention 9 CSF reabsorption 9.1 Arachnoidal outflow resistance 9.2 Arachnoid villi vs. olfactory drainage routes 9.3 Fluid reabsorption along spinal nerves 9.4 Reabsorption across capillary aquaporin channels 10 Developing translationally effective models for restoring CSF balance 11 Conclusion